2023
DOI: 10.1038/s41467-023-35907-4
|View full text |Cite
|
Sign up to set email alerts
|

A natural biological adhesive from snail mucus for wound repair

Abstract: The discovery of natural adhesion phenomena and mechanisms has advanced the development of a new generation of tissue adhesives in recent decades. In this study, we develop a natural biological adhesive from snail mucus gel, which consists a network of positively charged protein and polyanionic glycosaminoglycan. The malleable bulk adhesive matrix can adhere to wet tissue through multiple interactions. The biomaterial exhibits excellent haemostatic activity, biocompatibility and biodegradability, and it is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 62 publications
3
69
0
Order By: Relevance
“…The result presents the percent atomic concentrations of C, O, N, and S in SMu to be 52.21, 29.63, 8.65, and 0.49%, respectively, similar to Cru, C (54.99%), O (27.44%), N (9.3%), and S (0.82%), as reported in Table . The elements Cl, Ca, Mg, Na, K, and S were also identified, with Cl, Ca, and Mg as the most abundant after C, O, N, and S. This is consistent with the findings of Deng et al in their recent report . Meanwhile, metals have been reported to play essential roles in stabilizing snail mucus as a gel; therefore, similar functions may be attributed to the presence of these metals (Mg, Na, and Ca) in SMu and Cru.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The result presents the percent atomic concentrations of C, O, N, and S in SMu to be 52.21, 29.63, 8.65, and 0.49%, respectively, similar to Cru, C (54.99%), O (27.44%), N (9.3%), and S (0.82%), as reported in Table . The elements Cl, Ca, Mg, Na, K, and S were also identified, with Cl, Ca, and Mg as the most abundant after C, O, N, and S. This is consistent with the findings of Deng et al in their recent report . Meanwhile, metals have been reported to play essential roles in stabilizing snail mucus as a gel; therefore, similar functions may be attributed to the presence of these metals (Mg, Na, and Ca) in SMu and Cru.…”
Section: Resultssupporting
confidence: 90%
“…8 In a separate study, Deng et al did not find transition metals in their analysis of A. fulica mucus; instead, they found that Ca 2+ and Mg 2+ were the most abundant metals in the gastropod mucus. 59 The XPS elemental analysis indicates that no transition metal was detected in the Cru and SMu, according to Table 2; this is in line with the findings of Deng et al 59 Although they performed the elemental analysis using energydispersive X-ray spectroscopy (EDS). Werneke et al analyzed the elemental composition of H. aspersa with inductively coupled plasma atomic emission spectroscopy (ICP-AES) and EDS.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…15,16 Fibrous proteins and polysaccharides are the main components of snail mucus. 16 The sulfate, carboxyl, and hydroxyl groups are mostly responsible for the strong adhesion between gel and tissues. 16 A natural biological adhesive matrix from snail mucus has been characterized and applied in skin wounds, which showed excellent activity in adhesion and wound healing.…”
Section: Introductionmentioning
confidence: 99%